EXPERIMENTAL STUDY OF SOLAR CHIMNEY PERFORMANCE FOR PASSIVE HEATING (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2018)
An experimental investigation on solar chimney used for heating under climate of Iraqis carried out. Experiments were conducted on the chimney installed on vertical wall withabsorber plate placed at the front side of the air gap. The solar chimney attached to room ofdimensions (2.5×1.29×1.07) m. The chimney is studied to measure the effect of the air gapwidth with constant height of (1.07 m). Three widths are tested, namely, 0.2 m, 0.3 m and0.4 m. The experimental results showed that the solar chimney can achieve about (13 °C)difference in temperature between indoor and outdoor as well as it gives acceptabledifference in partial cloudy days. The results also indicated that the best performance ofsolar chimney is with 0.3m air gap width.